Palestinian Women in Decision-Making and Leadership Positions - Nahil S.E Abuhalib; Ahamad Faosiy Ogunbado (Yayasan Literasi Kita Indonesia, 2023)
The issue of women's participation in leadership and decision -making positions is one of the issues that sparked controversy over the past decades, due to the importance of empowering women in the highest positions, and equality between them and men in such opportunities based on the conviction that the process of comprehensive development and community construction requires effective participation from all society. With the different circumstances and challenges that Palestinian society went through, Palestinian women emphasized the effectiveness of their role as mothers and fighters, and they were able to prove their ability to fight all forms of struggle, whether political, social or military, but were they able, despite all these sacrifices, to reach their goal in leadership positions? This research tries to show the sacrifices of Palestinian women, and to investigate leadership positions and decision -making centers that they were able to reach today in the Palestinian reality. In this research, the descriptive method was used, and the most prominent results reached is that the proportion of women in the Palestinian cabinet is not only unstable, but the percentage has decreased significantly; This reality clearly shows the differences between women and men, despite the international laws did not distinguished between women and men gender or color.